Origin and Future of Plasmonic Optical Tweezers - Jer-Shing Huang; Ya-Tang Yang (Nanomaterials, 2015)
Plasmonic optical tweezers can overcome the diffraction limits of conventional optical tweezers and enable the trapping of nanoscale objects. Extension of the trapping and manipulation of nanoscale objects with nanometer position precision opens up unprecedented opportunities for applications in the fields of biology, chemistry and statistical and atomic physics. Potential applications include direct molecular manipulation, lab-on-a-chip applications for viruses and vesicles and the study of nanoscale transport. This paper reviews the recent research progress and development bottlenecks and provides an overview of possible future directions in this field.